Importance of Carbon Dioxide in the Isolation of Pneumococci - Austrian, Robert (1966)
Austrian, Robert (The University of Pennsylvania School of Medicine, Philadelphia), and Patricia Collins. Importance of carbon dioxide in the isolation of pneumococci. J. Bacteriol. 92:1281–1284. 1966.—Of the strains of pneumococci isolated from man, 8% manifest a requirement for CO(2) if detectable growth is to occur on the surface of solid media. The pneumococci most frequently manifesting this requirement are types I, III, XVI, XXVIII, and XXXIII. These strains will grow in the presence or absence of oxygen provided the atmosphere in which they are incubated contains CO(2). Review of published data provides no unequivocal evidence for the existence of anaerobic pneumococci.